Ioxynil and diethylstilbestrol disrupt vascular and heart development in zebrafish. (March 2019) - Li, Yi-Feng; Canário, Adelino V.M.; Power, Deborah M.; Campinho, Marco A.
Abstract: Background: Endocrine disruption is one of the consequences of industrialization and chemicals released into the environment have a profound impact on organisms. Waterborne micromolar concentrations of ioxynil (IOX) and diethylstilbestrol (DES) in fish affect the development of the heart, vasculature and thyroid gland. Objectives: The present study aimed to determine how IOX and DES disrupt the crosstalk between the developing thyroid gland and cardio-vascular system in zebrafish. Methods: Twelve hours post fertilization (hpf) wild type, Tg ( fli1:GFP ) or Tg ( cmalc2:GFPCaaX ) zebrafish embryos were exposed to 0.1 μM IOX or DES for 36 h (up until 48 hpf) or 60 h (up until 72 hpf). Embryos were used for vascular endothelial cell sorting, whole-mount immunohistochemistry, tissue selective transcriptomics, selected gene expression analysis by quantitative real-time polymerase chain reaction analysis and determination of heart rate by live imaging. Results: Exposure of zebrafish embryos to IOX and DES (0.1 μM) increased heart beat frequency and reduced ventricle volume and aorta diameter. The transcriptome of endothelial cells from blood vessels of hypertrophic, dilated and arrhythmogenic right ventricular cardiomyopathy was significantly changed and compound-specific toxic effects were found in IOX and DES exposed embryos. Both DES and IOX directly affected vascular and heart development and this indirectly impaired thyroid gland development in zebrafish. Even though the toxicity end-point of the two chemicals was similar, their action seemed to be via different gene regulatory pathways and physiological mechanisms. Conclusion: IOX and DES directly disrupt cardiovascular development and there is an associated disruption of thyroid tissue that most likely has long term consequences for this endocrine axis. Highlights: Exposure to IOX and DES (0.1 μM) impairs heart function and morphology in zebrafish. IOX and DES have common and compound-specific effects on endothelial cells. IOX and DES directly impair the vasculature and heart and indirectly impair thyroid gland. IOX and DES are thyroid disrupting compounds.